Analisis Faktor-Faktor Yang Mempengaruhi Produksi Petani Kentang (Solanum Tuberosum L) Di Desa Nagalingga, Kecamatan Merek, Kabupaten Karo - Siahaan, Jesi Tiara Lestari; Harahap, Gustami (Universitas Medan Area, 2026)
Potatoes (Solanum tuberosum L) are one of the most important horticultural commodities with high economic value and play a crucial role in improving farmers’ income in highland areas. This study aims to: (1) analyze the factors that influence potato production in Nagalingga Village, Merek District, Karo Regency; and (2) determine the effect of land area, labor, capital, seeds, fertilizers, and pesticides on farmers’ production levels. The analytical method used in this study was the Cobb-Douglas production function with multiple linear regression analysis. The results showed that land area, labor, capital, seeds, fertilizers, and pesticides simultaneously had a significant effect on potato production. Partially, the land area was found to have the most dominant influence on production increase. The coefficient of determination (R²) value of 0.992 indicates that these independent variables are able to explain 99.2% of the variation in potato farmers’ production levels.